EXAMINING TYPES OF MEANING IN ACEHNESE CONTEMPORARY SONG LYRICS: A STUDY OF APACHE13’S ALBUM BÉK PANIK - Fata, Ika Apriani; Yusuf, Yunisrina Qismullah; Khairi, Ziaul; Salmani Nodoushan, Mohammad Ali (LLT Journal: A Journal on Language and Language Teaching, 2024)
This study investigates the meanings embedded within song lyrics from the Acehnese local band Apache13’s album Bék Panik (translated as ‘Don’t Panic’). The primary aim is to analyze the types of meaning present in these Acehnese songs using a semantic approach. The objectives are to identify and categorize meanings based on six distinct types: conceptual, social, affective, collocative, connotative, and associative. The qualitative analysis of the song lyrics revealed 186 distinct meanings. Conceptual meaning was the predominant type, with a majority of instances, followed by social meaning, affective meaning, collocative meaning, and connotative meaning. Notably, no occurrences of associative meaning were found. The prevalence of conceptual meaning in the lyrics suggests a focus on social criticism, conditions, and personal narratives within Apache13’s songs. Conversely, the limited use of connotative meaning aligns with a preference for direct and explicit expression among Acehnese youth, reflecting contemporary cultural norms. This study contributes to understanding the nuanced meanings conveyed through contemporary Acehnese music, reflecting generational differences in expressive language use.